(untitled) (Research, Society and Development, 2024)
The testicle of the dog is an oval reproductive gland located in the scrotum, responsible for the production of sperm and sex hormones, such as testosterone. However, in some situations, there is a failure in the descent of one or both testicles into the scrotum during embryonic and fetal development or shortly after birth, characterizing cryptorchidism, which is one of the most common congenital anomalies in dogs. This condition has significant implications for the reproductive health and well-being of affected dogs, as well as presenting challenges for breeding and selection of breeders. Based on this, this work aims to describe the anatomy of the dog’s testicle and its development, as well as present the anatomical changes associated with cryptorchidism and the clinical implications of this condition for the health of these animals, through a literature review. Understanding the normal anatomy of the male reproductive system and the changes associated with cryptorchidism is essential for proper diagnosis, management, and genetic counseling. The etiology of cryptorchidism in dogs is multifactorial, involving genetic and environmental components. Additionally, endocrine disorders, maternal factors, exposure to endocrine disruptors, and other environmental influences during gestation can also contribute to the occurrence of this anomaly, which is as frequent as it is concerning in the care of dogs.